2021
DOI: 10.1007/s12144-021-02290-6
|View full text |Cite
|
Sign up to set email alerts
|

COVID-19 and social wellbeing in Malaysia: A case study

Abstract: The world has witnessed the largest single disruption to social wellbeing since the first known case of coronavirus disease 2019 (COVID-19) was reported in China in December 2019. In Malaysia, the government implemented the Movement Control Order (MCO) on 18 March 2020 in response to the COVID-19 pandemic. Thus, this paper highlights how the Malaysian government responded to COVID-19 in comparison with some Asian countries; and what has and has not worked for the MCO imposed by the government. The paper adopts… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
24
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 27 publications
(24 citation statements)
references
References 41 publications
(45 reference statements)
0
24
0
Order By: Relevance
“…Whereas, a small proportion of these respondents were on campus with limited f2f classes and maximum usage of the online medium for teaching and learning purposes as part of the Ministry of Higher Education’s effort to minimize the risk of Covid-19 infection among students. Online learning is the enabling factor for Malaysia success in combating the pandemic (Yong & Sia, 2021 ).…”
Section: Methodsmentioning
confidence: 99%
“…Whereas, a small proportion of these respondents were on campus with limited f2f classes and maximum usage of the online medium for teaching and learning purposes as part of the Ministry of Higher Education’s effort to minimize the risk of Covid-19 infection among students. Online learning is the enabling factor for Malaysia success in combating the pandemic (Yong & Sia, 2021 ).…”
Section: Methodsmentioning
confidence: 99%
“…The survey indicates that self-employed households will experience adverse shocks during a pandemic or other disasters that lead to an economic crisis. The other study conducted by Yong and Sia (2021) revealed that the COVID-19 pandemic has significant impacts on society's wellbeing in Malaysia, the most severe of which are adverse mental health and job unemployment.…”
Section: Socio-economic Impactmentioning
confidence: 99%
“…The Prime Minister of Malaysia then announced a movement control order (MCO) as an effort to curb the spread of the pandemic. Although initially the countermeasures and policies were useful to contain the pandemic, which prompted the Malaysian government to ease restrictions under MCO, a local election in Sabah incidentally prompted the second wave of COVID-19 in Malaysia [4]. Fortunately, the vaccines for the virus have been developed and are distributed all over the globe to curb the pandemic as soon as possible.…”
Section: Introductionmentioning
confidence: 99%